2023
DOI: 10.1039/d3ta05233h
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically robust cubic MnCoOx solid solution: achieving high activity for sustainable acidic water oxidation

Jingjing Zhang,
Ali Raza,
Yang Zhao
et al.

Abstract: This article reveals the promising potential of MnCoOx solid solutions as an effective catalyst for the oxygen evolution reaction (OER). The solid oxide solution was synthesized by utilizing redox deposition...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…The Ti 2p 3/2 XPS spectrum can be simplified into two peaks at 459.0 and 457.9 eV, which are attributed to Ti 4+ and Ti 3+ species. , The Ti 3d spectra indicated that the percentage of surface Ti 3+ in the VTiO x composites ranged from 12.2 to 23.0%, with the predominant titanium state being Ti 4+ . The O 1s XPS peaks were deconvoluted into three peaks, corresponding to lattice oxygen, oxygen trapped by vacancies (O v ), and hydroxyl groups, respectively. The O v number in the prepared VTiO x composite was determined to be much higher than that in pristine TiO 2 , with V 0.07 Ti 0.93 O x exhibiting the highest O v content of ∼24.4%. The XPS results demonstrate that the introduction of V leads to a partial reduction of Ti 4+ to Ti 3+ and the generation of additional oxygen vacancy sites, thereby enhancing the photocatalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…The Ti 2p 3/2 XPS spectrum can be simplified into two peaks at 459.0 and 457.9 eV, which are attributed to Ti 4+ and Ti 3+ species. , The Ti 3d spectra indicated that the percentage of surface Ti 3+ in the VTiO x composites ranged from 12.2 to 23.0%, with the predominant titanium state being Ti 4+ . The O 1s XPS peaks were deconvoluted into three peaks, corresponding to lattice oxygen, oxygen trapped by vacancies (O v ), and hydroxyl groups, respectively. The O v number in the prepared VTiO x composite was determined to be much higher than that in pristine TiO 2 , with V 0.07 Ti 0.93 O x exhibiting the highest O v content of ∼24.4%. The XPS results demonstrate that the introduction of V leads to a partial reduction of Ti 4+ to Ti 3+ and the generation of additional oxygen vacancy sites, thereby enhancing the photocatalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of the elemental valence state of CMR-x, the high-resolution X-ray photoelectron spectroscopy (XPS) spectra and fitted peaks are depicted in Figures g–i and S1. As for the high-resolution spectrum of Co 2p (Figure g), the Co 2+ (∼781.9 and ∼797.0 eV) and Co 3+ (∼779.8 and ∼795.0 eV) can be deconvoluted. , Moreover, the average values for surface oxidation state (SOS) of Co 2p for CMR-1, CMR-2, and CMR-3 are calculated based on the peak area, corresponding to ∼2.64, ∼2.56, and ∼2.66, respectively. In regard to the high-resolution spectrum of Mn 2p (Figure h), which can be divided into three kinds of peaks assigned to Mn 2+ (∼641.2 and ∼652.8 eV), Mn 3+ (∼642.2 and ∼655.2 eV), and Mn 4+ (∼644.8 and ∼656.6 eV), the average SOS values of Mn 2p for CMR-1, CMR-2, and CMR-3 are ∼2.49, ∼2.50, and ∼2.45, respectively.…”
Section: Structure and Chemical Compositionmentioning
confidence: 99%
“…As for the high-resolution spectrum of Co 2p (Figure g), the Co 2+ (∼781.9 and ∼797.0 eV) and Co 3+ (∼779.8 and ∼795.0 eV) can be deconvoluted. , Moreover, the average values for surface oxidation state (SOS) of Co 2p for CMR-1, CMR-2, and CMR-3 are calculated based on the peak area, corresponding to ∼2.64, ∼2.56, and ∼2.66, respectively. In regard to the high-resolution spectrum of Mn 2p (Figure h), which can be divided into three kinds of peaks assigned to Mn 2+ (∼641.2 and ∼652.8 eV), Mn 3+ (∼642.2 and ∼655.2 eV), and Mn 4+ (∼644.8 and ∼656.6 eV), the average SOS values of Mn 2p for CMR-1, CMR-2, and CMR-3 are ∼2.49, ∼2.50, and ∼2.45, respectively. Additionally, the difference in average SOS value between Co and Mn is 0.06 for CMR-2, which is smaller than those of CMR-1 (0.15) and CMR-3 (0.21), which is probably caused by the interfacial binding force between RuO 2 and CoMnO 3 .…”
Section: Structure and Chemical Compositionmentioning
confidence: 99%
“…For instance, doping elements (Ni, Co, Ru, etc. ), 19–21 developing novel structures (Co 2 MnO 4 , Mn 7.5 O 10 Br 3, etc. ), 14,22,23 regulating the phase (amorphous-MnO 2 , α-MnO 2 , γ-MnO 2 , etc. )…”
Section: Introductionmentioning
confidence: 99%